2011
DOI: 10.1002/cmdc.201100239
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Pharmacological Studies on Enantiomerically Pure p‐Methoxytacripyrines, Promising Multi‐Target‐Directed Ligands for the Treatment of Alzheimer’s Disease

Abstract: Alzheimer's disease (AD) is an age-related neurodegenerative process characterized by progressive memory loss and other cognitive impairments.[1] Although the etiology of AD is not well known, several factors such as amyloid-b (Ab) [2] deposits, t-protein aggregation, oxidative stress or low levels of acetylcholine [3] are thought to play significant roles in the pathophysiology of the disease.[4] In spite of the continuous efforts of the pharmaceutical industry and academia, an efficient strategy for the trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…In a recent work it was stated that chirality was an important feature of methoxytacripyrines as inhibitors. [35] Analyzing the published data, however, led us to the conclusion that the activity differences between the enantiomers or racemic mixtures, while considerably high for h AChE inhibition, were rather insignificant (<10 %) for Aβ assembly given the experimental error of the fibril growing and analytical processes. Chiral compounds in our current set of molecules are included in Groups II and V. The results obtained with these compounds support our earlier conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent work it was stated that chirality was an important feature of methoxytacripyrines as inhibitors. [35] Analyzing the published data, however, led us to the conclusion that the activity differences between the enantiomers or racemic mixtures, while considerably high for h AChE inhibition, were rather insignificant (<10 %) for Aβ assembly given the experimental error of the fibril growing and analytical processes. Chiral compounds in our current set of molecules are included in Groups II and V. The results obtained with these compounds support our earlier conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…The AutoDock Vina docking procedure used was previously validated. 62 Molecular Docking of Inhibitors 16 and 18 into eqBuChE and hBuChE. The horse BuChE model has been retrieved from the SWISS-MODEL Repository.…”
Section: ■ Methodsmentioning
confidence: 99%
“…Hence, the investigation of the activity profile of single enantiomers is of mandatory importance in order to elucidate the mechanisms of interaction and identify structural features involved in ligand‐target recognition. In the light of these considerations, in 2011 some of the authors published a new work in which they described the production of single enantiomers with high enantiomeric excess (ee>98 %) by chiral resolution of the ( R / S )‐4′‐methoxytacripyrine ITH122 , using a semi‐preparative high‐performance liquid chromatography (HPLC) approach on a chiral stationary phase . The absolute configuration at C4 was assigned by the X‐ray diffraction analysis of the two isolated fractions.…”
Section: Tacrine‐dihydropyridine Hybridsmentioning
confidence: 99%
“…In the light of these considerations, in 2011 some of the authors published a new work in which they described the production of single enantiomers with high enantiomeric excess (ee > 98 %) by chiral resolution of the (R/S)-4'-methoxytacripyrine ITH122, using a semi-preparative high-performance liquid chromatography (HPLC) approach on a chiral stationary phase. [16] The absolute configuration at C4 was assigned by the X-ray diffraction analysis of the two isolated fractions. The 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 evaluation of the anti-ChE activity of the two enantiomers revealed that chirality at the stereocenter C4 modulated the activity toward both ChEs, resulting the (S)-enantiomer ten folds more potent on AChE than the (R)-enantiomer.…”
Section: Tacripyrinesmentioning
confidence: 99%
See 1 more Smart Citation